IRPA GUIDANCE—THE ROLE OF STAKEHOLDERS, RADIATION PROTECTION CULTURE AND ETHICS IN EMERGENCY PREPAREDNESS. Issue 1 (25th August 2018) - Cantone, Marie-Claire; Coates, Roger; Le Guen, Bernard
Abstract: The International Radiation Protection Association, IRPA, promotes the excellence in radiation protection by providing benchmarks of good practice, as well as enhancing professional competence and networking. In relation to emergency situations, including post-accident and recovery phases, a key issue is the ability of the system of protection to take a broader view of societal values, along with the need to develop processes which support and respect the dignity and well-being of the affected populations. Regarding the various situations of radiation exposure, IRPA's activities include aspects which can contribute to medical preparedness in radiation emergencies, focusing particularly on stakeholder engagement, radiation protection culture, the ethical dimensions of radiation protection and public understanding of risks. As it is a combination of science, experience, ethical and social values, radiation protection culture promotes radiation risk awareness in the different exposure situations, including the implementation of countermeasures in radiation and nuclear emergencies and post-accident situations, with attention also on medical countermeasures.